2019
DOI: 10.1016/j.bbamcr.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of the amino acid transporter B0,+ (SLC6A14) to the plasma membrane involves an exclusive interaction with SEC24C for its exit from the endoplasmic reticulum

Abstract: A plasma membrane amino acid transporter B0,+ (ATB0,+), encoded by the SLC6A14 gene, is specific for neutral and basic amino acids. It is up-regulated in several types of malignant cancers. Neurotransmitter transporters of the SLC6 family interact with specific SEC24 proteins of the COPII complex along their pathway from the endoplasmic reticulum (ER) to Golgi. This study focused on the possible role of SEC24 proteins in ATB0,+ trafficking. Rat ATB0,+ was expressed in HEK293 cells, its localization and traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…In a model structure of LeuT bacterial transporter glycosylation sites were found at the second extracellular loop, a localization confirmed by crystallization of SERT in which N-acetylglucoseamine electron density were found to be linked to Asn moieties of the second extracellular loop (Coleman et al, 2016). As shown by Kovalchuk et al (2019), ATB 0,+ overexpressed in HEK293 cells was sensitive to deglycosylating enzymes: peptide-N 4 -(acetyl-β-glucosaminyl)asparagine amidase (PNGase F, EC 3.5.1.52) and endoglycosidase (Endo H, EC 3.2.1.96), confirming the presence of glycosylated form of the transporter in the plasma membrane.…”
Section: Slc6a14 -A Transporter With Broad Substrate Specificitymentioning
confidence: 75%
See 2 more Smart Citations
“…In a model structure of LeuT bacterial transporter glycosylation sites were found at the second extracellular loop, a localization confirmed by crystallization of SERT in which N-acetylglucoseamine electron density were found to be linked to Asn moieties of the second extracellular loop (Coleman et al, 2016). As shown by Kovalchuk et al (2019), ATB 0,+ overexpressed in HEK293 cells was sensitive to deglycosylating enzymes: peptide-N 4 -(acetyl-β-glucosaminyl)asparagine amidase (PNGase F, EC 3.5.1.52) and endoglycosidase (Endo H, EC 3.2.1.96), confirming the presence of glycosylated form of the transporter in the plasma membrane.…”
Section: Slc6a14 -A Transporter With Broad Substrate Specificitymentioning
confidence: 75%
“…As shown by Kovalchuk et al (2019), SLC6A14 co-localizes with calnexin, moreover, the core-glycosylated species of the transporter, characterized by lower M r than the fully glycosylated one can be detected by Western blot. Inhibition of SLC6A14 exit from ER results in accumulation of coreglycosylated transporter and directs the protein to ER-associated protein degradation (ERAD) (Kovalchuk et al, 2019). The further glycosylation steps take place in Golgi apparatus and lead to fully glycosylated protein (Moremen et al, 2012) which from trans-Golgi is trafficked in the vesicles to the plasma membrane.…”
Section: Regulation Of Slc6a14mentioning
confidence: 89%
See 1 more Smart Citation
“…In the endoplasmic reticulum, the quality control of SLC6A14 folding involves interactions with the heat shock proteins HSP70 and HSP90 [20]. SLC6A14 trafficking from the endoplasmic reticulum to the Golgi apparatus depends on its interaction with the cargo-recognizing protein SEC24 isoform C and the coatomer II (COPII) complex [21]. Further studies are needed to fully understand the mechanisms allowing SLC6A14 trafficking to the plasma membrane.…”
Section: Slc6a14 Expression and Regulation In The Lung And Gastrointementioning
confidence: 99%
“…In the latter, one possible explanation may be the involvement of Wfs1 in ER stress (Yamada et al 2006;Fonseca et al 2010;Cagalinec et al 2016), associated with the unfolded protein response where Wfs1 may influence protein synthesis and folding of the plasmalemmal NCX1. Supporting this concept, trafficking of the amino acid transporter B 0,+ (SLC6A14) to the plasma membrane involves an exclusive interaction with SEC24C for its exit from the ER (Kovalchuk et al 2019), where the Wfs1 also may be a part of this pathway. More focused to the cardiac myocytes and ion transporters, group of Wang et al (2018) has demonstrated recently, that protein MOG1 is involved in the regulation of the ER exit of cardiac sodium channel Na v 1.5 in neonatal rat cardiomyocytes.…”
mentioning
confidence: 99%